Covalent triazine-based framework: A promising adsorbent for removal of perfluoroalkyl acids from aqueous solution. (September 2016) - Wang, Bingyu; Lee, Linda S.; Wei, Chenhui; Fu, Heyun; Zheng, Shourong; Xu, Zhaoyi; Zhu, Dongqiang
Abstract: Perfluoroalkyl acids (PFAAs) are highly stable, persistent, and ubiquitous in the environment with significant concerns growing with regards to both human and ecosystem health. Due to the high stability to both biological and chemical attack, the only currently feasible approach for their removal from water is adsorbent technology. The main objective of this study was to assess a covalent triazine-based framework (CTF) adsorbent for removal from aqueous solutions of perfluoro C4, C6, and C8 carboxylates and sulfonates including the two C8s most commonly monitored, perfluorooctanoic acid (PFOA) and perfluorooctane sulfonate (PFOS). Adsorption affinity and capacity were quantified and compared to three commonly used sorbents: pulverized microporous activated carbon, single-walled carbon nanotubes, and Amberlite IRA-400 anion-exchange resin. CTF adsorbent exhibited pronouncedly higher adsorption affinity and capacity of PFAAs than other test sorbents. The remarkably strong adsorption to CTF can be attributed to the favored electrostatic interaction between the protonated triazine groups on the inner wall of the hydrophobic CTF pore and the negatively charged head groups of the PFAAs intercalated between the CTF layers. The homogeneous, nanosized pores (1.2 nm) of CTF hindered adsorption of a large-sized dissolved humic acid, thus minimizing the suppression of PFAA adsorption. Additionally, regeneration of CTF was easily accomplished by simply raising pH > 11, which inhibited the electrostatic adsorptive interaction of PFAAs. Graphical abstract: Highlights: CTF exhibits strong adsorption of PFAAs with varying chain length. CTF is a superior adsorbent to activated carbon, carbon nanotubes and resin. Electrostatic interaction is the dominant driving force for sorption to CTF. Homogeneous, nanosized pores of CTF minimize fouling by humic acid. Regeneration of CTF can be easily accomplished by simply raising pH > 11. Abstract : CTF is a promising adsorbent for perfluoroalkyl acids due to the unique homogeneous nanopore structures with pH-dependent adsorption activity.